PHYSIOLOGICAL RESPONSES OF SOME TREE SPECIES UNDER ROADSIDE POLLUTION IN KALUPUR AREA OF AHMEDABAD, GUJARAT (International Association of Biologicals and Computational Digest, 2023)
Plants can be used to mitigate increasing air pollution from vehicular exhaust by planting them along roadside. The present study focuses on the changes on physiological parameters selected tree species growing along road passing through Kalupur fruit market and Vimal Park society, Ahmedabad, Gujarat. The leaf samples of four trees were collected observe some physiological and biochemical parameters including pH of the leaf extract, Relative Water Content, Stomatal index, and Total Chlorophyll. Result of study showed that Ficus religiosa has the highest pH of leaf extract at polluted site, Azadirachta indica has highest total chlorophyll compared to non-polluted and Polyalthia longifolia has highest Stomatal index and RWC.
Keywords: Air pollution, stomatal index, RWC, pH, Total Chlorophyll, Azadirachta indica, Polyalthia longifolia, Alstonia scholaris, Ficus religiosa